Lag analysis of the effect of air pollution on orthopedic postoperative infection in Hebei Province and Xinjiang Uygur Autonomous Region - Shihang Liu; Shuai Zhou; Yonglong Li; Li Cao; Gang Lv; Libin Peng; Wei Chen; Lin Liu; Yingze Zhang; Hongzhi Lv (Scientific Reports)
Abstract To investigate the population distribution characteristics of hospitalized patients with postoperative fracture infections in Hebei Province and Xinjiang Uygur Autonomous Region, and to analyze the effects of air pollutants on postoperative fracture infections within the two regions. Data on orthopedic postoperative infection cases were retrospectively collected from representative hospitals in Hebei Province and the Xinjiang Uygur Autonomous Region from 2018 to 2022. Their distribution characteristics were analyzed using descriptive epidemiological methods. The lagged effects of air pollutants on postoperative infections were also evaluated using distributed lag nonlinear modeling, combined with air quality data from the same period. The rate of postoperative infections after orthopedic surgery in the Xinjiang Uygur Autonomous Region (3.06%) was significantly higher than that in the Hebei Region (0.47%) in this study. A total of 1338 patients with postoperative infections were collected from the two regions, with a mean age of 51.41 ± 17.34 years. The most affected age group was 41–60 years (521 cases, 39%), and there was a male predominance (875 cases, 65.40%). Using the air pollutant P50 as the reference concentration, the greatest cumulative 3-day increase in the risk of postoperative infection was observed for each 0.1 mg/m3 increase in CO concentration (RR = 1.069, 95% CI 1.029, 1.110). The greatest cumulative 12-day effect was observed for each 10 μg/m3 increase in NO2 concentration (RR = 1.67, 95% CI 1.369, 2.037). CO and NO2 showed reduced effects at very low concentrations and elevated effects at very high concentrations. The rate of postoperative infections after orthopedic surgery in the Xinjiang Uygur Autonomous Region was significantly higher than that in the Hebei Region. In Xinjiang, postoperative infections were predominantly observed in males aged 41–60 years. Exposure to air pollutants such as CO and NO2 increased the risk of postoperative orthopedic infections to varying degrees, with both short-term and cumulative lagged effects.